Chapter 10. Minor Vegetable Crop Production - Dakshina R. Seal; Qingren Wang; Ramdas Kanissery; Eugene J. McAvoy; Richard N. Raid; Crystal A. Snodgrass; Julien Beuzelin; Johan Desaeger; Shouan Zhang (EDIS)
Chapter 10 of the Vegetable Production Handbook.